Paramagnetic Meissner effect in ZrB12 single crystal with non-monotonic vortex–vortex interactions - Jun-Yi Ge; Vladimir N Gladilin; Nikolay E Sluchanko; A Lyashenko; Volodimir B Filipov; Joseph O Indekeu; Victor V Moshchalkov (New Journal of Physics, 2017)
The magnetic response related to the paramagnetic Meissner effect (PME) is studied in a high quality single crystal ZrB _12 with non-monotonic vortex–vortex interactions. We observe the expulsion and penetration of magnetic flux in the form of vortex clusters with increasing temperature. A vortex phase diagram is constructed, and shows that the PME can be explained by considering the interplay among the flux compression, the different temperature dependencies of the vortex–vortex and the vortex–pin interactions, and thermal fluctuations. Such a scenario is in good agreement with the results of magnetic relaxation measurements.